THE DESCRIPTION NAMING OF SUB-VILLAGE AND CULTURAL VOCABULARY DIVERSITY AT BAWODESOLO VILLAGE - Zendrato, Nicky Elvin Cristin; Telaumbanua, Nita Trima Niat; Waruwu, Mewi Dinda Arcila; Lawolo, Arni Yanti; Harefa, Afore Tahir (SIGEH ELT : Journal of Literature and Linguistics, 2024)
This research aims to describe the naming of sub-villages and the diversity of cultural vocabulary in Bawodesolo Village, Gunungsitoli District, Gunungsitoli City, North Sumatra Province. The focus of this research is on three sub-villages: Delafiga, Hilinangea, and Simanaere. Using a phenomenological research design, this study involves semi-structured interviews with local residents to understand the meanings and cultural contexts of these sub-village names. The results of the research show that the sub-village names reflect the cultural identity, history, and values of the local community. Names such as "Delafiga" and "Simanaere" are not only geographical markers but also hold historical narratives and cultural concepts that are significant to the community. The analysis of cultural vocabulary reveals that the terms used by the residents reflect their relationship with the environment, spiritual beliefs, and social practices. This study highlights the importance of toponymy in understanding cultural identity and suggests that regional development policies should consider the cultural values embedded in place names. This research contributes to the preservation of local cultural heritage and provides valuable insights for further studies on cultural dynamics in this area.